Generation and maintenance of acentric stable double minutes from chromosome arms in inter-species hybrid cells - Noriaki Shimizu; Rita Kapoor; Shuhei Naniwa; Naoto Sakamaru; Taku Yamada; You-ki Yamamura; Koh-ichi Utani (BMC Molecular and Cell Biology, 2019)
Abstract Background Extrachromosomal acentric double minutes (DMs) contribute to human malignancy by carrying amplified oncogenes. Recent cancer genomics revealed that the pulverization of defined chromosome arms (chromothripsis) may generate DMs, however, nobody had actually generated DMs from chromosome arm in culture. Human chromosomes are lost in human-rodent hybrid cells. Results We found that human acentric DMs with amplified c-myc were stable in human-rodent hybrid cells, although the degree of stability depended on the specific rodent cell type. Based on this finding, stable human-rodent hybrids were efficiently generated by tagging human DMs with a plasmid with drug-resistance gene. After cell fusion, human chromosomes were specifically pulverised and lost. Consistent with chromothripsis, pulverization of human chromosome arms was accompanied by the incorporation into micronuclei. Such micronucleus showed different replication timing from the main nucleus. Surprisingly, we found that the hybrid cells retained not only the original DMs, but also new DMs without plasmid-tag and c-myc, but with human Alu. These DMs were devoid of telomeres and centromeres, and were stable in culture for more than 3 months. Microarray analysis showed that the new DMs were generated from several human chromosomal regions containing genes advantageous for cellular growth. Such regions were completely different from the original DMs. Conclusions The inter-species hybrid mimics the chromothripsis in culture. This is the first report that experimentally demonstrates the generation of multiple stable acentric DMs from the chromosome arm.